2008
DOI: 10.1126/science.1152488
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Self-Sterility in a Hermaphroditic Chordate

Abstract: Hermaphroditic organisms avoid inbreeding by a system of self-incompatibility (SI). A primitive chordate (ascidian) Ciona intestinalis is an example of such an organism, but the molecular mechanism underlying its SI system is not known. Here, we show that the SI system is governed by two gene loci that act cooperatively. Each locus contains a tightly linked pair of polycystin 1-related receptor (s-Themis) and fibrinogen-like ligand (v-Themis) genes, the latter of which is located in the first intron of s-Themi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
125
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 141 publications
(127 citation statements)
references
References 27 publications
(33 reference statements)
0
125
0
Order By: Relevance
“…The minimum number of loci that can explain these six clusters under the assumption of ''haploid-sperm hypothesis'' is two polymorphic SI loci. Harada et al (1) than found two genetic markers that segregated in similar manner, one on chromosome 2q and the other on 7q. Fine mapping narrowed the search regions and, among the transcription units situated in these regions of the chromosomes, they suggested two polycystin-1-like (PDK1) genes that code for transmembrane receptors, as the putative SI genes.…”
Section: The Ascidiacea Urochordatamentioning
confidence: 99%
See 3 more Smart Citations
“…The minimum number of loci that can explain these six clusters under the assumption of ''haploid-sperm hypothesis'' is two polymorphic SI loci. Harada et al (1) than found two genetic markers that segregated in similar manner, one on chromosome 2q and the other on 7q. Fine mapping narrowed the search regions and, among the transcription units situated in these regions of the chromosomes, they suggested two polycystin-1-like (PDK1) genes that code for transmembrane receptors, as the putative SI genes.…”
Section: The Ascidiacea Urochordatamentioning
confidence: 99%
“…the primary sperm receptors, is located in the vitelline coat (VC) -the matrix surrounding the egg. (1,(11)(12)(13) Self sterility probably results from the failure of the sperm to bind to the VC of the autologous eggs. (14) However, self-sterility is not absolute and some are self-fertile.…”
Section: The Ascidiacea Urochordatamentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies have demonstrated that a similar system of the allogenic authentication (that utilizes gamete coat/membrane-associated proteins) is also present in animal hermaphrodite organisms (e.g. ascidian) (Harada et al 2008). Whether such animal system involves protein kinase signaling is unknown.…”
Section: Stigmatic S Receptor Kinase (Srk)mentioning
confidence: 99%